150k views
13 votes
(n-1 +7) simplify plssss helppp

User Tessie
by
5.2k points

2 Answers

12 votes

Answer: n+6

-1 + 7 = 6

So therefore, the answer is n+6

Hope this helped

User BlackJoker
by
5.3k points
9 votes

Answer:


  • \boxed{\sf{n+6}}

Explanation:

To solve this problem, first, you have to do is isolate it on one side of the equation.

(n-1+7)

First, remove parentheses.

→ n-1+7

Add the numbers from left to right.

→ -1+7=6

→ n+6

  • Therefore, the final answer is n+6.

I hope this helps you! Let me know if my answer is wrong or not.

User Qqwy
by
5.7k points